Analisis Peranan Audit Mutu Internal Sebagai Alat Bantu dalam Menunjang Efektivitas Manajemen pada STMIK STIKOM Indonesia - Ayu Gede Willdahlia (Jurnal Penjaminan Mutu, 2017)
Educational institutions are one of the growing organizations with the complexity of existing problems. Started from applying Tri Darma Perguruan Tinggi, where lecturers are required to be able to carry out teaching activities, research and dedication to the sustainable society every year. In addition to the activities undertaken in campus environment as a whole that already underway requires an evaluation conducted to maintain the quality. In addition, management also requires and goals to be achieved. A tool for evaluating and monitoring activities and can be used as a prevention tool and a decision maker in problem solving that occurs. Internal audit is a tool used in STMIK STIKOM Indonesia to ensure the activities at the institution have been run in accordance with the procedures they have. The institute hopes to improve management effectiveness in every field. Mismatch implementation of the procedure that occurs is a problem that must be overcome to know how effective internal audit quality is done so as to improve the effectiveness of management in solving existing problems. From the problems disclosed, the author tries to conduct research on STMIK STIKOM Indonesia. The purpose of this study is to find out how effective the implementation of Internal Audit existing in the institution and to know the role of Internal Audit in supporting the achievement of effectiveness in STMIK STIKOM Indonesiamanagement. The research was conducted by analyzing Internal Audit system at STMIK STIKOM Indonesia. The research phase starts from literature study then continued with data collection needed in research. After all the data collected proceed with the analysis. Based on the results of questionnaires dissemination and hypothesis testing conducted, that the implementation of internal audit in STMIK STIKOM Indonesia has been adequate and internal audit also play a role in supporting the effectiveness of the implementation of ISO 9001: 2008 quality management system. Itsconcluded that the presence of adequate internal audit will assist management in achieving the effectiveness of the implementation of ISO 9001: 2008 quality management system.